Breast cancer mortality in brazilian women between 2009 and 2019 (Research, Society and Development, 2023)
Breast cancer or mammary neoplasia reveals a serious public health problem in the world, due to its high incidence, morbidity and mortality and high treatment costs Objective: to know the epidemiological profile of breast cancer mortality in Brazilian women between the years from 2009 to 2019. Methodology: descriptive epidemiological research study, with a quantitative approach, with secondary database available in the Mortality Information System through the Department of Informatics of the Unified Health System. Data refer to deaths of Brazilian women from breast cancer. Results: 6,322 deaths were registered, the highest rates observed occurred in the South and Southeast regions and the lowest rates in the North region. The age group with the highest number of deaths in all regions was between 50-59 years old, the white variable was the highest in three regions (Southeast, South and Midwest), and in terms of schooling and marital status, the highest rate occurred in women with secondary education and in married women. Conclusion: Breast cancer mortality is still increasing in the country, and the South and Southeast regions had higher mortality rates than other regions. It is concluded that by knowing the profile of breast cancer mortality in Brazilian women, it is intended to contribute to the development and specific effectiveness for disease control and mortality prevention, through the strengthening of health care.